Ethnomathematics and Native Language in Teacher Education with Indigenous Peoples (Interdisciplinary Studies Journal, 2024)
The Ethnomathematics Program investigates the nature of mathematical knowledge in its historical, political, epistemological, conceptual, cognitive, and educational dimensions. Recognizing and valuing the knowledge and practices of different ethnic groups are sine qua non conditions for research in the field of Indigenous Teacher Education. This article aims to discuss the educational dimension of Ethnomathematics from the perspective of Indigenous teacher training. The theoretical framework is based on Ethnomathematics as a research program. The methodology was conducted through a participatory qualitative research, centered on an activity that aims to establish the relationship between mathematical language and mother tongue. The results indicate contributions to the teaching and learning of mathematics from a bilingual/multilingual, intercultural, community-based, and self-determination perspective; and reveal praxis in the initial training of teachers related to dynamic curricula, the dialogue of knowledge, and pedagogical strategies inspired by Indigenous sociocultural diversity. It concludes that the educational dimension of Ethnomathematics presents a possibility for dialogue between scientific and ancestral knowledge in the production of school knowledge within traditional communities.
Keywords: Indigenous Ethnomathematics; Cultural Diversity; Bilingualism/Multilingualism; Teaching; Learning